A method for preparing a memristor by electrochemical anodic oxidation
Patent Information
- Application Number
- CN202311164341.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-09-11
AI Technical Summary
[0005]本发明的目的在于提出一种用电化学制备忆阻器阻变层的方法,使用电化学方法对金属层进行部分氧化,得到金属氧化物层,最终制成阻变稳定、一致性和均一性较好的具有交叉结构的忆阻器件,从而解决现有技术中忆阻器件稳定性、一致性和均一性不佳的技术问题
[0021](1)本发明提供了一种使用电化学阳极氧化制备忆阻器氧化层的方法。相比于传统物理方式制备氧化层,此种方法不需要严苛的真空度、气氛条件,也不需要高额的能量消耗,可以以更低的能量消耗和时间成本制备金属氧化层,提高了制备忆阻器器件的效率。
Smart Images

Figure CN117279487B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the fields of semiconductor devices and electrochemical technology, and more specifically, relates to a method for preparing memristors using electrochemical anodic oxidation. Background Technology
[0002] Since 2008, when HP Labs first fabricated a memristor, proving the existence of the "fourth passive basic circuit element" proposed by Professor Tsai Shao-tang, the vast potential of memristors has attracted the attention of scientists worldwide.
[0003] In recent years, memristors have become a research hotspot in information storage and neuromorphic computing. The human brain consists of approximately 10... 11 One neuron through 10 15 Synapses connect to each other, forming a complex neural network that integrates information storage and computation. Inspired by the human brain, scientists have proposed various models of artificial neural networks. The basic units of a neural network—neurons and synapses—can be simulated using a single memristor instead of a CMOS device composed of dozens of transistors and capacitors. Therefore, by using memristor arrays, we can achieve higher-density integration of synapse or neuron arrays, ultimately improving the computational and energy efficiency of artificial neural networks.
[0004] While the fabrication and testing of individual memristors often do not require high consistency and uniformity, fabricating a memristor array of a certain scale on a single silicon wafer necessitates that each memristor exhibit repeatable and similar resistive switching behavior to better control the array or perform calculations. The traditional physical deposition process for growing thin films directly on a sample is not only costly and energy-intensive, requiring high vacuum and atmospheric conditions, but also results in randomly distributed oxygen vacancy defects in the metal oxide film. This causes the conductive filaments in filament-type memristors to randomly conduct under bias voltage, leading to significant randomness in the resistive switching behavior and thus considerable variability in the device's resistive switching process. In contrast, electrochemical anodizing of metal layers eliminates the requirements for vacuum and atmospheric conditions, consumes less energy, and yields denser, more uniform oxide films with a gradient of oxidation degree and higher quality. Because the oxide thin film formed by this method has a gradient of oxidation degree from the surface to the bottom electrode, the conductive filaments tend to conduct within the same oxidation degree region, thus making the resistive switching behavior of the device more consistent. This method of device fabrication can improve the uniformity and consistency of the device, and is more time-saving and labor-saving than physical methods. It can realize higher density memristor arrays, which is of great significance for the realization of related neural network functions. Summary of the Invention
[0005] The purpose of this invention is to propose a method for preparing the resistive switching layer of a memristor using electrochemical methods. The method involves partially oxidizing a metal layer using electrochemical methods to obtain a metal oxide layer, and finally fabricating a memristor device with a cross structure that exhibits good resistive switching stability, consistency, and uniformity. This solves the technical problem of poor stability, consistency, and uniformity of memristor devices in the prior art.
[0006] According to the present invention, a method for fabricating a memristor using electrochemical anodic oxidation is provided, comprising the following steps:
[0007] (1) Use photolithography to lithographically and develop the bottom electrode pattern on the substrate, and then deposit the bottom electrode;
[0008] (2) Photolithography and development of the metal layer pattern on the bottom electrode obtained in step (1), and then deposition of the metal layer;
[0009] (3) Using the sample obtained in step (2) as the anode and the inert metal electrode as the cathode, perform anodic oxidation in the electrolyte so that the part of the metal layer away from the bottom electrode is oxidized into metal oxide, and the degree of oxidation of this part of the oxidized metal layer is distributed in a gradient.
[0010] (4) The metal oxide obtained in step (3) is photolithographically etched and developed to form the top electrode pattern, and then the top electrode is deposited to prepare a memristor with a cross electrode structure.
[0011] Preferably, the thickness of the metal layer in step (2) is greater than 60 nm and less than 300 nm;
[0012] If the voltage of the anodizing in step (3) is 15-60V and the anodizing time is 60-240s, the oxidation degree is high and the resulting memristor is a volatile memristor with electronic conduction; if the voltage of the anodizing in step (3) is 10-25V and the anodizing time is 10-25s, the oxidation degree is low and the resulting memristor is a non-volatile memristor with oxygen vacancy filament conduction.
[0013] Preferably, in step (2), the metal layer is tantalum, titanium, niobium, hafnium or zinc.
[0014] Preferably, the electrolyte in step (3) is an acid, alkali or salt solution with a concentration range of 0.05-2 M / L.
[0015] Preferably, the bottom electrode is platinum, palladium, or gold, and the thickness of the bottom electrode is 20-50 nm.
[0016] Preferably, the bottom electrode is platinum, gold, ruthenium, or palladium, and the top electrode has a thickness of at least 50 nm.
[0017] Preferably, the deposition methods in steps (1), (2) and (4) are each independently selected from physical magnetron sputtering or atomic layer deposition.
[0018] Preferably, the bottom electrode in step (1) is a bottom electrode array; the metal layer in step (2) is a metal layer array; and the top electrode in step (4) is a top electrode array.
[0019] According to another aspect of the present invention, a memristor or memristor array prepared by the method is provided.
[0020] In summary, compared with the prior art, the above-described technical solutions conceived by this invention can achieve at least the following beneficial effects:
[0021] (1) This invention provides a method for preparing a memristor oxide layer using electrochemical anodic oxidation. Compared with traditional physical methods for preparing oxide layers, this method does not require stringent vacuum or atmospheric conditions, nor does it require high energy consumption. It can prepare metal oxide layers with lower energy consumption and time cost, thereby improving the efficiency of memristor device preparation.
[0022] (2) The preparation method of the present invention can control the thickness and oxidation degree of the oxide film by adjusting the oxidation voltage, oxidation time, and electrolyte solution type and concentration during the anodic oxidation process. The oxidation process in the present invention only oxidizes a portion of the upper layer of the oxidized metal layer, without completely transforming the metal layer into an oxide layer, thus retaining a portion of the lower metal layer. Based on the control of the oxidation process, such as the oxidation time, on the degree of oxidation of the oxide layer, the present invention can obtain a non-volatile memristor at a lower oxidation degree and a volatile memristor at a higher oxidation degree.
[0023] (3) The preparation method of the present invention is suitable for preparing various memristors with metal oxide as resistive switching layer, and has strong universality. It is also suitable for the preparation of large-scale memristor arrays.
[0024] (4) The memristor oxide layer prepared by this invention is denser, has a smoother surface, and the degree of oxidation gradually decreases uniformly from top to bottom. This makes the migration of ions or vacancies more concentrated in the same region during the resistive switching process, resulting in more consistent resistive switching on a macroscopic scale. This improves the consistency of memristor devices, enhances their resistive switching behavior, and is more conducive to the control and computation of memristor arrays. Consequently, its application in neural networks has a broader prospect.
[0025] (5) The preparation method proposed in this invention can fabricate memristor devices with different performances by simply adjusting parameters such as electrolyte solubility and type, oxidation time, and oxidation voltage. The upper metal layer is partially oxidized, while the lower metal layer is retained. This allows for the fabrication of non-volatile memristors to simulate synaptic functions when the oxidation degree of the upper metal is low, and also enables the fabrication of volatile memristors to simulate neuronal functions when the oxidation degree of the upper metal is high.
[0026] (6) This method can make memristors have more consistent resistive switching behavior, which is more conducive to the large-scale integration of memristor arrays. Attached Figure Description
[0027] Figure 1 This is a schematic diagram of the vertical and horizontal structures of the memristor in the method of the present invention.
[0028] Figure 2 This is a schematic diagram of the array structure of the memristor in the method of the present invention.
[0029] Figure 3 This is a simplified schematic diagram of the anodizing platform of the present invention.
[0030] Figure 4 This is a comparison chart of IV cycle tests between the tantalum oxide-based memristor obtained by magnetron sputtering using physical methods in Comparative Example 1 and the tantalum oxide-based memristor obtained by anodizing in Example 1.
[0031] Figure 5 This is the memristor simulated synaptic plasticity curve obtained in Example 1 of the present invention.
[0032] Figure 6 The image shows the IV characteristic curve of the titanium oxide-based non-volatile memristor obtained in Example 2.
[0033] Figure 7 These are the IV characteristic curves and conductance pulse response diagrams of the tantalum oxide-based volatile memristor obtained in Example 3. Detailed Implementation
[0034] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.
[0035] This invention discloses a method for fabricating memristors using electrochemical anodic oxidation. The method employs electrochemical oxidation to prepare the oxide layer of the memristor, thereby improving the density and uniformity of the resistive switching layer. Simultaneously, the degree of oxidation in the oxide layer gradually decreases from top to bottom. For non-volatile memristors, the formation and breakage positions of oxygen vacancy filaments are relatively constant during resistive switching, resulting in better consistency. The memristor adopts a classic "sandwich" structure in its vertical direction, i.e., two electrode layers sandwiching the resistive switching layer. In the horizontal direction, it employs a cross-electrode structure, with the bottom and top electrodes perpendicular to each other in planar projection.
[0036] The specific preparation steps are as follows:
[0037] (1) Clean the silicon wafer substrate with silicon oxide on the surface and blow it dry to obtain a surface suitable for thin film growth;
[0038] (2) Deposit bottom electrode pattern: Use photolithography to photolithographically form the bottom electrode pattern on the substrate and then grow the electrode film;
[0039] (3) Preparation of metal layer: First, the pattern of metal resistive switching layer is photolithographically printed on the sample, and then a metal layer of a certain thickness is deposited;
[0040] (4) Preparation of oxide layer: Place the sample at the anode and the inert metal electrode at the cathode, and place them together in the electrolyte and apply voltage stimulation for a certain period of time to obtain a metal oxide of a certain thickness.
[0041] (5) Fabrication of top electrode: The top electrode pattern is photolithographically patterned on the sample, and the top electrode is deposited to fabricate a memristor with a cross electrode structure.
[0042] In some embodiments, the specific steps of cleaning in step (1) are: placing the silicon wafer substrate in acetone, alcohol and deionized water in sequence, ultrasonically cleaning for 15 minutes each, and circulating three times, and finally drying with nitrogen gas.
[0043] In some embodiments, the patterns in steps (2), (3), and (5) are generated by photolithography and then deposited using physical magnetron sputtering or atomic layer deposition techniques after photolithography to prepare the electrode film.
[0044] In some embodiments, the bottom electrode in step (2) consists of a 3-5 nm titanium metal layer and a 20-50 nm platinum metal layer; wherein titanium can be replaced by materials with good adhesion to silicon wafers, such as tungsten, and platinum can be replaced by inert noble metals such as palladium and gold.
[0045] In some embodiments, in step (3), the metal layer material deposited using physical magnetron sputtering or atomic layer deposition technology can be a metal with resistive switching effect such as tantalum, titanium, niobium, hafnium, zinc, etc., and the deposition thickness should be greater than 60 nm and less than 300 nm, and then an oxide layer is prepared by anodic oxidation.
[0046] In some embodiments, step (3), the process of depositing a metal layer thin film using magnetron sputtering technology, specifically involves: mounting a metal layer target (such as a tantalum target) on the chamber target source, and then controlling the chamber vacuum at 2×10⁻⁶. -6 Torr below, Sputtering at a certain rate for 20-100 minutes yields a metal layer (such as a tantalum metal layer) with a thickness of at least 60 nm.
[0047] In some embodiments, in step (4), the oxide layer is obtained by electrochemically anolysing a pre-deposited metal film, placing it at the anode of a power source, and oxidizing it together with an inert metal cathode in an electrolyte solution under electrical stimulation. Different combinations of electrolyte solution concentration and type, oxidation voltage, and oxidation time can produce memristors with different volatile properties. High voltage and long oxidation time easily generate a more completely oxidized oxide film, thus producing a volatile device with tunneling effect, while low voltage or short time generates more oxygen vacancies, forming a non-volatile device with oxygen vacancy filament conduction. For example, in a 0.5M phosphoric acid solution, oxidizing 60nm tantalum metal at an oxidation voltage of 10-25V for 10-25s can produce a non-volatile memristor, while oxidizing at an oxidation voltage of 25-60V for 60-240s can produce a volatile memristor.
[0048] In some embodiments, an electrochemical anodic oxidation method is used, specifically: the electrolytic cell for anodic oxidation is an acid, alkali, or salt solution with a concentration range of 0.05-2 M / L; the oxidized metal can be a metal with resistive switching effect such as tantalum, titanium, niobium, hafnium, zinc, etc.; the inert electrode can be platinum, gold, palladium, ruthenium, graphite, etc.; the oxidation voltage is 10-50 V; and the oxidation time is 10-120 s.
[0049] In some embodiments, the top electrode in step (5) is composed of an inert metal layer, such as platinum, gold, ruthenium, palladium, etc. The thickness of the top electrode is at least 50 nm to prevent the step effect from causing a circuit break.
[0050] This invention can obtain a metal oxide layer with a gradient distribution of oxidation degree and a uniform surface, resulting in a memristor with a more uniform resistive switching layer and more consistent resistive switching behavior. Moreover, compared with the commonly used deposition methods, it does not require strict vacuum conditions, atmosphere conditions, etc., and can fabricate memristor devices and arrays in a lower cost and higher energy efficiency manner, thereby obtaining memristors with higher consistency.
[0051] The following are specific embodiments.
[0052] Example 1
[0053] This embodiment provides a method for fabricating a non-volatile tantalum oxide-based memristor with a cross-structure using an electrochemical anodic oxidation method. Figure 1 This is a schematic diagram of the vertical and horizontal structure of the memristor in the method of the present invention. TopElectrode (TE) is the top electrode, Bottom Electrode (BE) is the bottom electrode, and Resistive Layer (RL) is the resistive switching layer. Figure 2 This is a schematic diagram of the array structure of the memristor in the method of the present invention.
[0054] Includes the following steps:
[0055] Cleaning the silicon substrate: Immerse the silicon wafer in acetone, ethanol and deionized water, and ultrasonically clean each for 15 minutes for 3 minutes. After 3 cycles, dry it with a nitrogen air gun and set it aside.
[0056] Fabrication of the bottom electrode: After obtaining the bottom electrode pattern on the substrate using photolithography, the sample is placed on the tray of the magnetron sputtering cavity. Titanium and platinum targets are installed on the target source in the cavity, and the base vacuum of the cavity is evacuated to less than 2 × 10⁻⁶ Torr. Argon gas with a purity of 99.999% is introduced as the working gas, and the sputtering pressure is 3 mTorr. At a sputtering rate, a titanium metal layer with a thickness of 5 nm was sputtered and deposited, and then... The sputtering rate was adjusted to deposit a 20 nm thick platinum metal layer, which was then degummed to obtain the bottom electrode.
[0057] Preparation of the tantalum metal layer: After obtaining the resistive switching layer pattern on the sample using photolithography, the sample is placed on the tray of the magnetron sputtering cavity. A tantalum target is mounted on the target source in the cavity, and the base vacuum of the cavity is evacuated to less than 2 × 10⁻⁶ Torr. Argon gas with a purity of 99.999% is introduced as the working gas, and the sputtering pressure is 3 mTorr. At a sputtering rate of 1000 nm, sputtering for 20 minutes resulted in the deposition of a tantalum metal film with a thickness of 60 nm.
[0058] Preparation of the tantalum oxide layer: The sample was fixed with a conductive clamp and connected to the positive terminal of the power supply to form the anode. An inert platinum mesh electrode was then connected to the negative terminal of the power supply to form the cathode. Both were placed in a 0.5M phosphoric acid solution, and the electrolyte was stirred at 350 rpm using an electric stir bar. After setting the electrolytic cell conditions, the sample was oxidized for 18-20 seconds using 18-20V to partially oxidize the previously deposited tantalum metal layer, obtaining a tantalum oxide layer of approximately 30 nm. After oxidation, the sample was removed and degummed to obtain a complete resistive switching electrode. A schematic diagram of the anodic oxidation electrolytic cell equipment is shown below. Figure 3 As shown;
[0059] Fabrication of the top electrode: After obtaining the top electrode pattern on the substrate using photolithography, the sample is placed on the tray of the magnetron sputtering cavity. A platinum target is mounted on the target source in the cavity, and the base vacuum of the cavity is evacuated to less than 5 × 10⁻⁶ Torr. Argon gas with a purity of 99.999% is introduced as the working gas, and the sputtering pressure is 3 mTorr. The sputtering rate was used to deposit a 40 nm thick platinum metal layer, which was then degummed to obtain the top electrode.
[0060] Comparative Example 1
[0061] This comparative example prepares the substrate and bottom electrode using the same method as in Example 1. The difference is that after step (2), a tantalum oxide resistive switching layer is directly deposited using magnetron sputtering. After the resistive switching layer is prepared, the top electrode pattern is developed by photolithography, and then tantalum metal and platinum are deposited sequentially to complete the preparation of the top electrode. Specifically:
[0062] Fabrication of the resistive switching layer: After photolithography to develop the resistive switching layer pattern on the sample, it is placed on the tray of the magnetron sputtering cavity. A tantalum oxide target is installed on the target source in the cavity, and the cavity background vacuum is evacuated to less than 2 × 10⁻⁶. -6 Torr was used, with 99.999% pure argon gas as the working gas, a sputtering pressure of 3 mTorr, and an RF sputtering target of tantalum oxide. The sputtering rate was [missing information]. After deposition for 7 minutes, a tantalum oxide film with a thickness of at least 20 nm was obtained, followed by degumming.
[0063] Fabrication of the top electrode: After obtaining the top electrode pattern on the substrate using photolithography, the sample is placed on the tray of the magnetron sputtering cavity. Tantalum and platinum targets are mounted on the target source in the cavity, and the base vacuum of the cavity is evacuated to less than 5 × 10⁻⁶. -6 Torr, using 99.999% pure argon gas as the working gas, with a sputtering pressure of 3 mTorr, to At a certain sputtering rate, a 30 nm thick tantalum metal layer and a 20 nm thick platinum metal layer were successively sputtered and deposited, and then a debinding process was performed to obtain the top electrode.
[0064] Analysis and comparison of the memristors in Example 1 and Comparative Example 1:
[0065] Figure 4 This is a comparison chart of the IV cycle tests of the tantalum oxide-based memristor obtained by magnetron sputtering in Comparative Example 1 (using a physical method) and the tantalum oxide-based memristor obtained by anodizing in Example 1. The comparison shows that the consistency of the curve for 100 cycles in Example 1 is significantly higher than that of the curve for 50 cycles in Comparative Example 1. This indicates that the memristor device with the same type of resistive switching layer prepared using the electrochemical anodizing method achieves higher consistency than the device obtained by conventional magnetron sputtering.
[0066] Figure 5 This is a simulated synaptic plasticity curve of the tantalum oxide-based memristor obtained in Example 1 of the present invention. Figure 5 It can be seen that the fabricated device can effectively simulate some of the functions of a synapse.
[0067] Example 2
[0068] This embodiment provides a method for fabricating a non-volatile titanium oxide-based memristor with a cross-structure using an electrochemical anodic oxidation method, including the following steps:
[0069] Cleaning the silicon wafer substrate: Same as step (1) in Example 1.
[0070] Preparation of the bottom electrode: Same as step (2) in Example 1.
[0071] Preparation of the titanium metal layer: After obtaining the resistive switching layer pattern on the sample using photolithography, the sample is placed on the tray of the magnetron sputtering cavity. A titanium target is mounted on the target source in the cavity, and the background vacuum of the cavity is evacuated to less than 2 × 10⁻⁶. - 6 Torr, using 99.999% pure argon gas as the working gas, with a sputtering pressure of 3 mTorr, to At a sputtering rate of 1000 nm, sputtering for 50 minutes resulted in the deposition of a 60 nm thick titanium film.
[0072] Preparation of the titanium oxide layer: The electrolytic cell was set up in the same way as step (4) in Example 1. After the electrolytic cell conditions were set, the sample was oxidized for 15 seconds using a voltage of 18V, so that the upper part of the titanium metal layer was oxidized to obtain the titanium oxide layer, while the lower part retained the Ti metal layer. After oxidation, the sample was removed and degummed to obtain a complete resistive switching electrode.
[0073] Preparation of the top electrode: Same as step (5) in Example 1.
[0074] Figure 6 The figure shows the IV characteristic curves of the titanium oxide-based memristor obtained in Example 2. As can be seen from the figure, the experimentally prepared titanium oxide memristor exhibits stable resistive switching behavior.
[0075] Example 3
[0076] This embodiment provides a method for fabricating a volatile tantalum oxide-based memristor with a cross-structure using an electrochemical anodic oxidation method, including the following steps:
[0077] Cleaning the silicon wafer substrate: Same as step (1) in Example 1.
[0078] Preparation of the bottom electrode: Same as step (2) in Example 1.
[0079] Preparation of the tantalum metal layer: After obtaining the resistive switching layer pattern on the sample using photolithography, the sample is placed on the tray of the magnetron sputtering cavity. A tantalum target is mounted on the target source in the cavity, and the background vacuum of the cavity is evacuated to less than 2 × 10⁻⁶. - 6 Torr, using 99.999% pure argon gas as the working gas, with a sputtering pressure of 3 mTorr, to At a sputtering rate of 120 nm, a tantalum metal film with a thickness of 120 nm was deposited after sputtering for 40 minutes.
[0080] Preparation of tantalum oxide layer: The electrolytic cell was set up in the same way as step (4) in Example 1. After the electrolytic cell conditions were set, the sample was oxidized with a voltage of 30V for 120s to oxidize the upper part of the tantalum metal layer to obtain a tantalum oxide layer with a high degree of oxidation. After oxidation, the sample was taken out and degummed to obtain a complete resistive switching electrode.
[0081] Preparation of the top electrode: Same as step (5) in Example 1.
[0082] Figure 7 The figures show the IV characteristic curves and conductance retention test graphs of the tantalum oxide memristor obtained in Example 3. During the negative scan, a positive voltage is applied to the top electrode. As can be seen from the figures, the tantalum oxide memristor prepared in Example 3 exhibits stable volatile resistive switching behavior, and its conductance can automatically recover to its initial state within a short time after pulse adjustment.
[0083] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a non-volatile memristor using oxygen vacancy filament conduction via electrochemical anodic oxidation, characterized in that, Includes the following steps: (1) Use photolithography to photolithographically print and develop the bottom electrode pattern on the substrate, and then deposit the bottom electrode; (2) The pattern of the metal layer is photolithographically formed and developed on the bottom electrode obtained in step (1), and then the metal layer is deposited; (3) The sample obtained in step (2) is used as the anode and the inert metal electrode is used as the cathode. The anodization is carried out in the electrolyte. The voltage of the anodization is 10-25 V and the time of the anodization is 10-25 s. The part of the metal layer away from the bottom electrode is oxidized into metal oxide. The metal layer is not completely turned into an oxide layer. The metal near the bottom electrode is retained, and the degree of oxidation of the oxidized part of the metal layer is gradient. (4) The metal oxide obtained in step (3) is photolithographically etched and developed to form the top electrode pattern, and then the top electrode is deposited to prepare a non-volatile memristor with oxygen vacancy filament conduction with cross electrode structure.
2. The method for preparing a non-volatile memristor using oxygen vacancy filament conduction via electrochemical anodic oxidation as described in claim 1, characterized in that, The thickness of the metal layer in step (2) is greater than 60 nm and less than 300 nm.
3. The method for preparing a non-volatile memristor using oxygen vacancy filament conduction via electrochemical anodic oxidation as described in claim 1 or 2, characterized in that, In step (2), the metal layer is tantalum, titanium, niobium, hafnium or zinc.
4. The method for preparing a non-volatile memristor using oxygen vacancy filament conduction via electrochemical anodic oxidation as described in claim 1, characterized in that, The electrolyte in step (3) is an acid, alkali or salt solution with a concentration range of 0.05-2 mol / L.
5. The method for preparing a non-volatile memristor using oxygen vacancy filament conduction via electrochemical anodic oxidation as described in claim 1, characterized in that, The bottom electrode is made of platinum, palladium, or gold, and the thickness of the bottom electrode is 20-50 nm.
6. The method for preparing a non-volatile memristor using oxygen vacancy filament conduction via electrochemical anodic oxidation as described in claim 1, characterized in that, The top electrode is made of platinum, gold, ruthenium, or palladium, and the thickness of the top electrode is at least 50 nm.
7. The method for preparing a non-volatile memristor using oxygen vacancy filament conduction via electrochemical anodic oxidation as described in claim 1, characterized in that, The deposition methods in steps (1), (2) and (4) are each independently selected from physical magnetron sputtering or atomic layer deposition.
8. The method for preparing a non-volatile memristor using oxygen vacancy filament conduction via electrochemical anodic oxidation as described in claim 1, characterized in that, The bottom electrode in step (1) is a bottom electrode array; the metal layer in step (2) is a metal layer array; and the top electrode in step (4) is a top electrode array.
9. A non-volatile memristor with oxygen vacancy filament conduction prepared by any one of claims 1-7.
10. The non-volatile memristor array with oxygen vacancy filament conduction prepared by the method described in claim 8.
Citation Information
Patent Citations
Multifunctional memristor and regulation and control method thereof
CN114203900A
KR20230099784A